Adoption of Hygienic Practices at Fish Landing Centres and Markets - S., Balasubramaniam; J., Charles Jeeva; Srinath, Krishna (Fishery Technology, 2025)
The study was conducted at the fish landing centres in selected four districts of Kerala viz., Trichur, Alleppey, Ernakulam and Kannur, and the fish markets in Ernakulam district. In the case of landing centres, of the six practices evaluated among the fishermen, the adoption score was higher for only one practice viz., use of clean containers for fish handling (81.03%). Low level of adoption was observed on two practices viz., use of adequate clean water for washing fish (39.49%) and prompt system of waste disposal (40.00%). The overall adoption index was 54.96%. The 'F' test results revealed that the extent of adoption varied significantly among the fishermen in the four districts. The perception index for the impact of popularization efforts undertaken among fishermen was 55.26%. The R2 value indicated that all the variables put together served as a cause of 71.60% variation in the adoption level. In case of fish markets, the overall index for the availability of infrastructural facilities was 79.74%. The fish marketing personnel were well aware of all the seven hygienic practices studied, with the overall awareness index of 93.60%. Of the six hygienic practices measured, practices such as the use of clean containers or polythene sheets for keeping fish (89.55%), using adequate clean water for washing (98.51%), sorting of fish hygienically in a clean place (84.33%), using adequate ice for preventing fish spoilage (98.51%) and maintaining personal cleanliness and handling of the fish hygienically (94.78%), were adopted by majority of the respondents. Lower adoption was observed in the case of using prompt methods of waste disposal (68.66%). The regression analyses revealed that education positively influenced the extent of adoption among the fish marketing personnel.